2021
DOI: 10.3389/fmolb.2021.629873
|View full text |Cite
|
Sign up to set email alerts
|

Glycans of SARS-CoV-2 Spike Protein in Virus Infection and Antibody Production

Abstract: Viral protein glycosylation represents a successful strategy employed by the parasite to take advantage of host–cell machinery for modification of its own proteins. The resulting glycans have unneglectable roles in viral infection and immune response. The spike (S) protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), which presents on the surface of matured virion and mediates viral entry into the host, also undergoes extensive glycosylation to shield it from the human defense system. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
93
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(93 citation statements)
references
References 77 publications
0
93
0
Order By: Relevance
“… 54 Compared with Middle East respiratory syndrome coronavirus (MERS-CoV) and SARS-CoV, the S protein of SARS-CoV-2 has a lower glycosylation density, 35 , 63 , 327 indicating the S protein surface is more exposed and it is more effective in eliciting humoral immunity. 31 Since the first report of 16 N-linked glycosites by cryo-electron microscopy (cryo-EM), 320 the characterization of glycosylation of S protein becomes a hotspot. 38 , 62 , 63 , 70 , 145 , 328 336 In total, 23 N-linked glycosites with high occupancy (mostly >95%) have been reported (Fig.…”
Section: Introductionmentioning
confidence: 99%
“… 54 Compared with Middle East respiratory syndrome coronavirus (MERS-CoV) and SARS-CoV, the S protein of SARS-CoV-2 has a lower glycosylation density, 35 , 63 , 327 indicating the S protein surface is more exposed and it is more effective in eliciting humoral immunity. 31 Since the first report of 16 N-linked glycosites by cryo-electron microscopy (cryo-EM), 320 the characterization of glycosylation of S protein becomes a hotspot. 38 , 62 , 63 , 70 , 145 , 328 336 In total, 23 N-linked glycosites with high occupancy (mostly >95%) have been reported (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…From this, one can speculate why the virus has a high rate of transmission ( 27 ). Numerous studies have reported a glycan shield over the spike protein that might be somehow helping in the immunity evasion of the virus, but further work is still needed o confirm its role in immunity evasion ( 28 , 29 ). There is much more that needs to be discovered about this spike protein.…”
Section: Structural Characteristics Of Sars-cov-2mentioning
confidence: 99%
“…In vitro and in vivo experiments later revealed antiviral activity of cyanovirin-N against the Zaire strain of the Ebola virus (ZEBOV) based on its affinity towards envelope glycoproteins on the surface of the Ebola virus [40]. Pathogenic viruses take control of the host's cellular apparatus to implement their own replication processes, a strategy fortified by glycosylation [41]. The SARS-CoV-2 spike protein undergoes glycosylation to produce glycans that mask polypeptide epitopes and shield it from the innate immune response, and facilitate spike-ACE2 interaction [41,42].…”
Section: Molecular Docking Of the Cyanobacterial Proteins With The Receptor-binding Domain Of The Sars-cov-2 Spike Proteinmentioning
confidence: 99%
“…Pathogenic viruses take control of the host's cellular apparatus to implement their own replication processes, a strategy fortified by glycosylation [41]. The SARS-CoV-2 spike protein undergoes glycosylation to produce glycans that mask polypeptide epitopes and shield it from the innate immune response, and facilitate spike-ACE2 interaction [41,42]. The glycosylation of the SARS-CoV-2 spike protein produces 22 N-linked glycosylation sites that comprise two oligomannose-type, six oligomannose and complex-type and 14 complextype glycans [43,44].…”
Section: Molecular Docking Of the Cyanobacterial Proteins With The Receptor-binding Domain Of The Sars-cov-2 Spike Proteinmentioning
confidence: 99%
See 1 more Smart Citation